1952
DOI: 10.1104/pp.27.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Fractions, Respiration, and Structure of Normal and Crown Gall Tissues of Tomato

Abstract: IntroductionThe development of masses of tumorous tissue following implantation of Agrobacterium tumefaciens into susceptible plants has been of considerable interest to biologists for half a century. Among the many studies on these crown galls, few, however, have attempted to compare and correlate the structure and vital activities of normal and tumorous tissues from the time of inoculation through the various phases of development of the normal control plant and of the tumorous plant. For the tomato plant, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

1952
1952
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…ANALYTICAL METHODS Triplicate 1.5 gm samples of fresh leaf tissue (60 to 70 1-cm leaf punches) were fractionated into inorganic, soltuble organic, nucleic acid, and protein phosphorus by the procedures of .Juni et al (15) as modified by Klein (13). Lipid phosphorus, determined as above, is reported for ovtules and seed kernels, but it is included in the nucleic-acid fraction in the instance of leaves since preliminary trials had shown the lipid-P The water-culture solutions were changed at irregular intervals and extra P was added to the low-P solutions in order to support some growth of the plants.…”
mentioning
confidence: 99%
“…ANALYTICAL METHODS Triplicate 1.5 gm samples of fresh leaf tissue (60 to 70 1-cm leaf punches) were fractionated into inorganic, soltuble organic, nucleic acid, and protein phosphorus by the procedures of .Juni et al (15) as modified by Klein (13). Lipid phosphorus, determined as above, is reported for ovtules and seed kernels, but it is included in the nucleic-acid fraction in the instance of leaves since preliminary trials had shown the lipid-P The water-culture solutions were changed at irregular intervals and extra P was added to the low-P solutions in order to support some growth of the plants.…”
mentioning
confidence: 99%
“…Since there were no modifications in percentage dry weight, cell numbers, nitrogen content, nor any significant variations in the DNA of the host cells during the period of study (Klein, 1952;Klein et al, 1953), it may be concluded that these potential sources of error do not modify the results obtained on a dry weight basis. Since there were no modifications in percentage dry weight, cell numbers, nitrogen content, nor any significant variations in the DNA of the host cells during the period of study (Klein, 1952;Klein et al, 1953), it may be concluded that these potential sources of error do not modify the results obtained on a dry weight basis.…”
mentioning
confidence: 92%
“…A clue to its nature was provided by Klein (1952) who found that tomato stem tissues inoculated with Agrobacterium tumelaciens showed a high peak in the concentration of desoxyribonucleic acid (DNA) within 48 hr. A clue to its nature was provided by Klein (1952) who found that tomato stem tissues inoculated with Agrobacterium tumelaciens showed a high peak in the concentration of desoxyribonucleic acid (DNA) within 48 hr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insofar as nitrate-nitrogen nutrition pla ys a role in the causal complex of meristematic activity as ex pr essed by cell formation and by cell growth, it apparently is a factor in the causal complex of transformation of normal into tumor cells and of their subsequent growth and duplication (Klein and Link, 1952). Insofar as nitrate-nitrogen nutrition pla ys a role in the causal complex of meristematic activity as ex pr essed by cell formation and by cell growth, it apparently is a factor in the causal complex of transformation of normal into tumor cells and of their subsequent growth and duplication (Klein and Link, 1952).…”
mentioning
confidence: 99%